ISLAMIC BANK COMPLIANT HANDLING: UPAYA MEWUJUDKAN PENINGKATAN BANK SERVICE QUALITY DAN CUSTOMER RECOVERY SYSTEM - Fasa, Muhammad Iqbal; Sisdianto, Ersi; Ridwansyah, Ridwansyah; Susanto, Is; Idaman, Northa (ITB AAS Indonesia Surakarta, 2024)
This research attempt to develop previous research by offering novelty based on Islamic Bank compliant handling, bank service quality and customer recovery system at the Islamic People's Financing Bank of Lampung Province. The method used in this study uses a qualitative research approach. BPRS Bandar Lampung has handled complaints with several things: First, customers who do not approve (approval) financing due to changes in management. Second, customers who experience changes in the profit sharing ratio on sharia deposits at BPRS. What was done by BPRS Bandar Lampung was to apologize to related parties, then explain why this incident happened, and to provide good service quality by providing suggestions and objectives for customers at other banks offered while still being able to get the desired product. The implications obtained by BPRS Bandar Lampung: customers who were initially disappointed, became more accepting of the change in management at BPRS Bandar Lampung. Thus, the recovery of disappointed customers can be resolved properly. Thus, the hope is to increase customer loyalty and satisfaction continuously (sustainable)